Dynamic Response Evaluation of Damped-Outrigger Systems with Various Heights. Issue 2 (May 2017) - Huang, Bin; Takeuchi, Toru
Outriggers are a proven and effective system used to reduce the dynamic response of tall buildings. By inserting dampers into the outriggers, providing supplementary energy dissipation, further improvements in the dynamic response can be achieved. The aim of this study is to develop analytical methods for the dynamic response evaluation of a single-damped-outrigger system and determine the optimal outrigger locations and damper sizes to minimize response. Changes in the mode shape, damping, natural period and seismic response were studied parametrically using complex eigenvalue analysis of a continuous cantilever model, and the accuracy verified by comparison with a member-by-member model. A simplified single-degree-of-freedom model was then constructed and studied using an assumed lateral displacement curve and the principle of virtual work. Finally, a practical method for determining optimal outrigger location and damper size based on this simplified model was proposed.